The effect of individual selection on sperm motility in tropical abalone Haliotis squamata - Permana I. Gusti Ngurah; Suprapto Rommy; Gunawan; Sumarwan Joko; Nurejo Supono Panut; Mahardika Ketut; Julyantoro Pande Gde Sasmita (E3S Web of Conferences, 2023)
High-quality broodstock is required to support successful cultivation activities of the tropical abalone. This study aimed to find out the structure of the sperm under the influence of individual selection. A total of 50 eggs per batch were measured in egg diameter, calculated by the degree of fertilization and hatching rate. Sperm collection is carried out from the natural spawning of male abalone from the wild (F0) and the selected offspring from individual Fillial-1, F2, and F3 selections. Samples of sperm were collected by artificial spawning and analyzed using the Sperm Class Analyzer® CASA System. The results showed that the wild abalone (F0) had the highest hatching rate but was not significantly different from other derivatives (P > 0.05). The average spermatozoa was 2.39 million cells/m, with the highest spermatozoa (F0) of 7.110 million cells/ml. The most increased sperm motility and rapid velocity were in the wild (89.78%; 34.00%) and the lowest of F2 (22.00; 4.00%). A significant difference in sperm motility and rapid velocity were found between F0 and other treatment. The consequences of individual selection will aid in studying reproductive factors and sperm motility, which are most likely crucial in tropical abalone fertilization.